CELL-PENETRATING PEPTIDES NANO-CONJUGATED WITH METALLIC NANOPARTICLE FOR THE DEVELOPMENT OF THERAPEUTIC AND OR PROPHYLACTIC AGENTS AGAINST RESPIRATORY SYNCYTIAL VIRUS - Sharma, Homa Nath (International Journal of Research -GRANTHAALAYAH, 2023)
Respiratory Syncytial Virus (RSV) is an enveloped, pleomorphic, often filamentous, cytoplasmic virus-containing non-segmented, negative-sense, single-stranded RNA associated with viral proteins, making up a nucleocapsid core that is enclosed within a lipid envelope. RSV causes about 7 % of deaths among infants and young children globally, which is the second-most cause of mortality in that age group after malaria. Despite the immense impact mounted by RSV in public health and the economy, there are no effective prophylactic and therapeutic agents to control and treat the disease caused by RSV. Currently, four RSV vaccines and a monoclonal antibody candidate, all using the stabilized pre-fusion (F) proteins, have shown promising results in healthy subjects and are in phase III clinical trial. Results from these trials are expected to be released soon. However, more than one type of vaccine and therapeutics are required to cover all populations at risk: younger children, older adults, pregnant women, and immunocompromised people. Search for more antiviral drugs and vaccines is going on, but due to the issues of cost, toxicity, resistance, bioavailability, and overall pharmacokinetic profile associated with prospective traditional drugs, studies on antiviral peptides can offer novel avenues in the field. In recent years, cell-penetrating peptides (CPPs) with 5-30 AAs in length have shown promising drug delivery potential, but antiviral property demonstrated by some CPPs is another exciting possibility in the drug discovery arena, since finding shorter anti-viral peptides is another priority to minimize the cost. Some of the metallic nanoparticles have shown antiviral properties themselves. If both cell-penetrating property and antiviral activity can be found in the same peptide, nano-conjugating CPP with or without other antiviral peptides can improve the stability and other therapeutic indices of such peptide so that it can possibly be developed as safe and effective therapeutic and or prophylactic tools to control RSV.